EFEKTIVITAS EKSTRAK DAUN JATI ( TECTONA GRANDIS L. F) DALAM MENGHAMBAT PERTUMBUHAN JAMUR HORMISCIUM Sp. - Ni Putu Adriani Astiti (Environmental Research Center (PPLH) of Udayana University, 2015)
A research on effectiveness of extracts of teak (Tectona grandis L. f) leaves in inhibit thegrowth of a species of fungi, Hormiscium sp. has been carried out. The leaves used in thisresearch were young leaves (number 1 and 2), and old ones (number 5 and 6), with fourconcentrations: 0, 2, 5, and 10 %. The media utilised were bean sprouts agar, and thereplications was 3 times. Qualitative tests were undertaken for the flavonoids, while alkaloidtests were based on Culvenor Fitzgerald methods. Qualitative tests of triterpenoids andsteroids were undertaken by utilising Lieberman – Burchard reagents (L-B reagents).Parameters observed were colony diameters, micellium weights (dry mass), and numbers ofconidia (ml). Results of this research showed that extracts of teak (T. grandis) leaves wereable to inhibit the growth of Hormiscium sp. The capability of inhibitions was increased asthe extract concentrations increased (for both, that of the young and old leaves), eventhough extracts of the young provided a higher capability of inhibitions compared to theold ones.